Ribitol and ribose treatments differentially affect metabolism of muscle tissue in FKRP mutant mice - Marcela P. Cataldi; Qi L. Lu (Scientific Reports)
Abstract Dystroglycanopathy is characterized by reduced or lack of matriglycan, a cellular receptor for laminin as well as other extracellular matrix proteins. Recent studies have delineated the glycan chain structure of the matriglycan and the pathway with key components identified. FKRP functions as ribitol-5-phosphate transferase with CDP-ribitol as the substrate for the extension of the glycan chain. Supplement of ribitol and ribose have been reported to increase the levels of CDP-ribitol in both cells and in muscles in vivo. Clinical trials with both ribitol and ribose have been reported for treating LGMD2I caused by mutations in the FKRP gene. Here we compared the comprehensive metabolite profiles of the skeletal muscle between ribitol-treated and ribose-treated FKRP mutant mice. The closely related pentose and pentitol show clearly differential impacts on metabolisms despite their similarity in enhancing the levels of CDP-ribitol and matriglycan synthesis. Supplement of ribitol changes lysophospholipid sub-pathway metabolite profiling with a trend towards normalization as reported in the muscle after AAV9-FKRP gene therapy. Ribose treatment significantly increases level of ribonate and elevates levels of advanced glycation end products. Further analysis is required to determine which metabolite is prudent to use for long-term daily treatment of dystroglycanopathies.